Determinants of sustainable development goals in Sub-Saharan Africa: the roles of foreign direct investment inflows, environmental taxes, and natural resource rents - Ozcan, Burcu; Eryilmaz, Serkan; Zeren, Feyyaz (Springer, 2026)
This paper examines the influence of key economic variables-gross domestic product (GDP), foreign direct investment (FDI), environmental tax revenues (ETR), and natural resource rents (NRR)-on progress toward the Sustainable Development Goals (SDGs) in Sub-Saharan Africa (SSA) for the period 2010-2023. To reflect the complex and multidimensional nature of sustainability, financial development (FD) and institutional quality (IQ) are included as control variables. Financial development (FD) and institutional quality (IQ) are included as control variables to capture the complex nature of sustainability. The empirical analysis employs fixed-effects panel models with Driscoll-Kraay standard errors to account for heteroscedasticity, autocorrelation, and cross-sectional dependence. To address potential endogeneity and dynamic relationships, the two-step system Generalized Method of Moments (System GMM) estimator is applied as a robustness check. The results indicate that GDP, ETR, and FD have statistically significant positive effects on overall SDG performance, while FDI inflows, NRR, and weak IQ exert substantial adverse impacts. Disaggregated findings show that GDP enhances progress on social and economic goals, but is insufficient to address environmental and institutional dimensions. ETR contributes positively to climate action, industrial development, and well-being, but negatively affects SDG 15 (life on land). FDI and NRR are associated with negative externalities, supporting the pollution haven and resource curse hypotheses. This paper is the first to assess the impact of these variables across all 17 SDGs in SSA, offering new insights into the region's development dynamics. It provides critical implications for designing integrated policy strategies aimed at fostering inclusive growth, environmental sustainability, and institutional reform in alignment with the 2030 Agenda.
Keywords: Sustainable development; Sustainable development goals (SDGs); Foreign direct investment; Environmental taxes; Natural resource rents; Economic growth